Widespread horizontal transfer of mitochondrial genes in flowering plants - Bergthorsson, Ulfar; Adams, Keith L.; Thomason, Brendan; Palmer, Jeffrey D. (Nature (London), 2003)
Horizontal gene transfer—the exchange of genes across mating barriers—is recognized as a major force in bacterial evolution 1 , 2 . However, in eukaryotes it is prevalent only in certain phagotrophic protists and limited largely to the ancient acquisition of bacterial genes 3 , 4 , 5 . Although the human genome was initially reported 6 to contain over 100 genes acquired during vertebrate evolution from bacteria, this claim was immediately and repeatedly rebutted 7 , 8 . Moreover, horizontal transfer is unknown within the evolution of animals, plants and fungi except in the special context of mobile genetic elements 9 , 10 , 11 , 12 . Here we show, however, that standard mitochondrial genes, encoding ribosomal and respiratory proteins, are subject to evolutionarily frequent horizontal transfer between distantly related flowering plants. These transfers have created a variety of genomic outcomes, including gene duplication, recapture of genes lost through transfer to the nucleus, and chimaeric, half-monocot, half-dicot genes. These results imply the existence of mechanisms for the delivery of DNA between unrelated plants, indicate that horizontal transfer is also a force in plant nuclear genomes, and are discussed in the contexts of plant molecular phylogeny and genetically modified plants.